Stress and Coping Mechanism of Infertile Women Attending Infertility Clinic in Kathmandu - Sharma, Chandrakala; Subedi, D; Rai, L; Upreti, K (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Many women face problems related to infertility in various aspects of their life. Also, it is not comfortable to discuss on this issue. Because of this, the feelings and distress faced by women may not come out and the pent up emotions may lead to different stress related problems. MATERIAL AND METHODS : A descriptive research design was adopted to assess the stress and coping mechanism of infertile women attending infertility clinic in Kathmandu Nepal. The study was conducted from October 2011 to January 2013. Purposive sampling technique was used and sample size was 100. Data was collected through semi- structured interview using; 'Perceived Stress Scale'(PSS) and 'Coping Check List' (CCL). RESULTS: Regarding stress level of respondents, 40% were at very high level of stress and 35% with high level of stress. High level stress was found among the age group of 21-30 years. In relation to level of stress and coping strategies, 54.17% respondents with high stress used religious coping strategies, 50% of the respondents with very high stress also used religious coping, followed by 40% emotional coping and 37.5% problem focused coping and seeking social support strategies to overcome the stress. CONCLUSION: It can be concluded that the almost more than half of the respondents were under high level of stress and mostly were those who are under treatment for more than 1-3 yrs of duration. The study also concluded that the higher the age the respondents were more stressed due to the infertility. It was also found that most of the respondents used religious coping as well as emotional focused coping during the stressful period. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12039 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 24-28